Pressure injury: incidence in critical units of a regional hospital (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Objectives: Measuring the incidence of pressure injury (PI) in users hospitalized in critical units of a public reference institution in southwestern Bahia. Method: Prospective longitudinal study. Data were collected between June and August of 2017, through a direct interview, medical records, medical prescription and inspection of the participant’s skin. Results: Of the 83 participants, 39 (47%) developed PI. The medium stay in the study was 6.8 days. Most of them were male, black or brown and had low schooling. The mean age was 47.6 years (± 19.8). It was evidenced that the continuous use of vasoactive drugs and sedoanalgesia is associated with PI. Thirty-two (38.55%) participants presented a high risk for PI development. The calcaneal region (44%) was the most affected. The number of lesions per participant was 1.28, on average, with lesions in stage 1 (68%) predominating. The occurrence of an unfavorable outcome (death) was statistically significant. Conclusion: The multifactorial character of the emergence of PI requires the adoption of institutional measures focused on the prevention of this adverse event, and should be part of the process of permanent education of professionals.